A comparison between UWB and GPS devices in the measurement of external load and collective tactical behaviour variables during a professional official match - Rico-González, M.; Los Arcos, A.; Nakamura, F. Y.; Gantois, P.; Pino-Ortega, J. (International Journal of Performance Analysis in Sport, 2020)
The aim of the study was to compare the agreement of the data on the kinematic demands and collective tactical variables during a professional soccer match between GPS and UWB sensors. The data were extracted from a professional soccer match played in "the regular season" during 2019-2020. The analysis indicated a high-degree of agreement between UWB and GPS sensors to measure the total distance covered (ICC>0.94). In addition, Bland-Altman plots showed a low average difference for the total distance covered between the devices (mean difference = -0.011 to -0.017 m). Although the collective tactical variable (i.e. surface area) showed a high-degree of agreement between both devices (i.e. ICC>0.84), a significant main effect was found for the average difference between the UWB sensor and GPS sensor (mean difference = -9.25 to 57.41 m2). In addition, Bland-Altman plots showed a slight systematic bias for lower surface area measured by the GPS sensor in comparison to the UWB sensor. Researchers and technical staff should consider that the data provided by the GPS and UWB can be interchangeable in the analysed kinematic variables. However, the data provided by the devices cannot be compared in the analysed collective variables due to the differences found.